2019
DOI: 10.24251/hicss.2019.584
|View full text |Cite
|
Sign up to set email alerts
|

The Compromise of One’s Personal Information: Trait Affect as an Antecedent in Explaining the Behavior of Individuals

Abstract: This research examined the role trait affect, a lifelong and generally stable type of affect, has on the information security behavior of individuals. We examined this in the context of how one responds to the threat of one's personal information becoming compromised. This was done by extending Protection Motivation Theory (PMT) by incorporating the two higher order dimensions of affect, positive affect and negative affect, as antecedents to self-efficacy, perceived threat severity, and perceived threat vulner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Overall, 11.0% of the participants were successfully phished, which includes 5.7% of participants that identify as female and 19.3% of participants that identify as male. We conducted a chi-square test to determine if there was a significant difference based on gender and found that gender was related to the propensity to click on this phishing email, 2 (2, N = 146) = 6.73, p < .05.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 11.0% of the participants were successfully phished, which includes 5.7% of participants that identify as female and 19.3% of participants that identify as male. We conducted a chi-square test to determine if there was a significant difference based on gender and found that gender was related to the propensity to click on this phishing email, 2 (2, N = 146) = 6.73, p < .05.…”
Section: Resultsmentioning
confidence: 99%
“…The continued success of social engineering attacks is perhaps most evident in the use of and response to phishing emails. Despite the relatively long history of studying phishing and attempts to mitigate its effectiveness (e.g., [5]), it remains a significant challenge and threat for end users, including to their personal information [2]. There are many challenges associated with phishing email simulations.…”
Section: Introductionmentioning
confidence: 99%